A safety comparison of heparin and argatroban anticoagulation in veno-venous extracorporeal membrane oxygenation with a focus on bleeding - Burša, Filip; Máca, Jan; Sagan, Jiří; Sklienka, Peter; Němcová, Simona; Kučerová, Zuzana; Romanová, Tereza; Jor, Ondřej; Kondé, Adéla; Janošek, Jaroslav; Frelich, Michal (Transfusion medicine (Oxford, England), 2025)
BACKGROUND: Anticoagulation during extracorporeal membrane oxygenation (ECMO) might still lead to severe bleeding complications. Heparin is the most frequently used anticoagulant, but novel drugs could be promising. Argatroban is a new alternative to heparin. To date, no robust studies have confirmed the clear superiority of argatroban (AG) over heparin, although it has some advantages and may be safer. STUDY DESIGN AND METHODS: An observational study was conducted in all adult veno-venous ECMO patients with COVID-19-associated acute respiratory distress syndrome admitted to the University Hospital Ostrava (n = 63). They were anticoagulated with heparin in the first period and with AG in the second period, targeting the same activated partial thromboplastin time (aPTT; 45-60 s). Bleeding complications requiring transfusion and life-threatening bleeding events were evaluated. The primary objective was to compare heparin and AG in terms of bleeding, transfusion requirements and mortality-related bleeding. RESULTS: The total time on ECMO per patient was 16 days with an in-hospital mortality of 55.6%. The red blood cell consumption in the AG group (median 2.7 transfusions/week) was significantly lower than in the heparin group (median 4.2 transfusions/week, p = 0.011). Life-threatening bleeding complications were higher in the heparin group compared to the AG group (35.7% vs. 10.2%, p = 0.035), and mortality-related bleeding complications were also higher in the heparin group (21.4% vs. 2.0%, p = 0.032). DISCUSSION: Argatroban is an interesting alternative to heparin with less bleeding, less need for red blood cell transfusions and improved safety of ECMO with less mortality-related bleeding.
Keywords: dospělí; Hemorrhage; COVID-19; Extracorporeal Membrane Oxygenation; sulfonamidy; anticoagulation; krvácení; Humans; Arginine; lidé středního věku; Middle Aged; Pipecolic Acids; bleeding; arginin; mimotělní membránová oxygenace; Heparin; mužské pohlaví; Adult; kyseliny pipekolové; ženské pohlaví; heparin; argatroban; lidé; SARS-CoV-2; antikoagulancia; Anticoagulants; extracorporeal membrane oxygenation (ECMO); Aged; senioři; Male; Sulfonamides; Female